1993
DOI: 10.1007/bf01379090
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of monoclonal antibodies against hog cholera virus (Alfort 187 strain)

Abstract: Summary.A panel of 15 monoclonal antibodies (Mabs) against hog cholera virus (HCV) was produced and each Mab was characterized according to its viral protein specificity, virus-neutralizing activity and immunoreactivity with a large collection of HCV isolates.Hog cholera (HC) is a contagious and economically important disease of pigs and is caused by hog cholera virus (HCV). HCV belongs to the genus pestivirus of the family Flaviviridae [5]. This genus is composed of hog cholera virus, bovine viral diarrhoea v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As these monoclonal antibodies did not react in Western blot analyses [4], we could not yet determine against which of these proteins they are directed. By SDS-PAGE electrophoretic analyses in non-denaturing conditions, we observed not only the precipitation of a 65 kDa polypeptide which we assume is the disulfide linked dimer gp 15/16-gp 55, but also a 46 kDa protein formed by the disulfide linked dimer p 27-gp 15/16.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As these monoclonal antibodies did not react in Western blot analyses [4], we could not yet determine against which of these proteins they are directed. By SDS-PAGE electrophoretic analyses in non-denaturing conditions, we observed not only the precipitation of a 65 kDa polypeptide which we assume is the disulfide linked dimer gp 15/16-gp 55, but also a 46 kDa protein formed by the disulfide linked dimer p 27-gp 15/16.…”
Section: Discussionmentioning
confidence: 94%
“…Caij et al [4] demonstrated that this monoclonal antibody was not HCV restricted, but also recognized BVDV strains. It was previously demonstrated that the non-structural protein p 125 of the cytopathic N A D L strain of BVDV is cleaved to give rise to two proteins, the N-terminal product of 54 kDa and the Cterminal product of 80 kDa [6,19].…”
Section: Reactivity Of Anti-hcv Mabs With Bvd V Proteinsmentioning
confidence: 98%
See 1 more Smart Citation